Teaching and Learning Social Justice through Online Service-Learning Courses - Guthrie, Kathy L.; McCracken, Holly (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
Creating a virtual classroom in which diverse students feel welcome to discuss and experience topics related to social justice, action, and change is a study in the value of connectedness and collaboration. Through a combination of technologies, pedagogies, and on-site experiences, virtual cultures develop that encourage the formation of demanding yet stimulating learning environments in which communications and interactions are intellectually transformative. This article explores student perceptions of their participation in an online service-learning course while working in local service organizations. Qualitative methodology was used to identify the philosophical intersection at which multiple pedagogies meet: social justice, service-learning, civic engagement, and leadership as instructed in a web-based environment. This study illustrates the capacity for intentionally constructed online educational experiences focused on social justice, civic engagement, and leadership to affect learning and to provide educators with pedagogical best practices to facilitate requisite change in teaching practice.